1996
DOI: 10.1128/cmr.9.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the complement system by pathogenic fungi

Abstract: Fungi have been studied as prototype activators of the complement cascade since the early 1900s. More recently, attention has focused on the role of the complement system in the pathogenesis of fungal infections. The interactions of Cryptococcus neoformans and Candida albicans with the complement system are the most widely characterized; however, all pathogenic fungi examined to date have the ability to initiate the complement cascade. The molecular mechanisms for initiation and regulation of the complement ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(38 citation statements)
references
References 103 publications
(119 reference statements)
2
36
0
Order By: Relevance
“…To examine this, we used an antibody against C4d, a sensitive and reliable marker for complement deposition 13. Since pathogenic fungi have been reported to be potent inducers of complement activation cascade,14 pulmonary tissue from a patient with Aspergillus infection was tested in parallel as positive control (figure 4G). We found that no measurable C4d signal was obtained from the lungs of patients 1 and 2 (figure 4D, E) similar to normal control (figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…To examine this, we used an antibody against C4d, a sensitive and reliable marker for complement deposition 13. Since pathogenic fungi have been reported to be potent inducers of complement activation cascade,14 pulmonary tissue from a patient with Aspergillus infection was tested in parallel as positive control (figure 4G). We found that no measurable C4d signal was obtained from the lungs of patients 1 and 2 (figure 4D, E) similar to normal control (figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…albicans activates both the alternative and the classical pathway of complement [48], and the complement system is important in the resistance against disseminated and cutaneous candidiasis [49]. Antibodies protective against candidiasis require efficient deposition of complement on the fungal surface [50].…”
Section: Discussionmentioning
confidence: 99%
“…The host's response to C. neoformans infection is a complex interplay between cytokine regulation and cellular and humoral immunity, with the complement system playing a major role. The activation of the alternative pathway by encapsulated C. neoformans not only favors its opsonization by phagocytic cells [15][16][17] but also enhances the cytokine production induced by this fungus [18,19].…”
mentioning
confidence: 99%